The Knowledge Economy-finance nexus: how do IPRs matter in SSA and MENA countries? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
This paper assesses the relevance of intellectual property rights (IPRs) in the knowledge economy (KE)-finance nexus using the four variables identified under the World Bank's knowledge economy index (KEI) and seven financial intermediary dynamics of depth, efficiency, activity and size. Three main findings are established: (1) education increases financial dynamics of depth and size; (2) economic incentives by means of credit facilities (trade openness) mitigate financial dynamics of efficiency and activity (financial dynamics of depth and size) and; (3) ICT and FDI both improve financial depth and decrease financial size (with FDI having an additional edge of improving financial activity). As a policy implication, the enforcement of IPRs is not a general and sufficient condition for positive KE-finance nexuses. Hence, blanket upholding of IPRs to achieve such positive linkages may not be successful unless policy is contingent on the prevailing 'KE specific component' trends and dynamics of financial development.
Keywords: K42; O10; O34; O38; P48; 330; Financial development; Knowledge economy; Intellectual property rights